Pendampingan Pembelajaran Daring dalam Meningkatkan Kreativitas Anak Usia Dini - Ida Ayu Made Yuni Andari; Ida Ayu Putri Genta Widyasari (IAHN Gde Pudja Mataram, 2022)
The Covid-19 pandemic has delayed all lines of education. There are many schools that are forced to carry out online learning. In this service, what is desired is online learning assistance to foster early childhood creativity by presenting the material and then the child expresses the material through drawing things that are in the child's imagination. The approach model in learning used is project based learning. Early childhood looks very enthusiastic in participating in the activities of the service team, and are able to produce an image from the imagination of the child and the child can present what the child has drawn and colored according to the child's wishes on picture book media.